2005
DOI: 10.1007/s10646-005-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

A Test Battery Approach for the Ecotoxicological Evaluation of Estuarine Sediments

Abstract: The purpose of this study was to evaluate the overall sensitivity and applicability of a number of bioassays representing multiple trophic levels, for the preliminary ecotoxicological screening (Tier I) of estuarine sediments. Chemical analyses were conducted on sediments from all sampling sites to assist in interpreting results. As sediment is an inherently complex, heterogeneous geological matrix, the toxicity associated with different exposure routes (solid, porewater and elutriate phases) was also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 54 publications
2
31
0
1
Order By: Relevance
“…from different trophic and organizational levels [23,[35][36][37]. Tuikka et al [23], who investigated seven natural sediments using a test battery similar to that of the present study (SCTs with invertebrates, fish, and bacteria), demonstrated differences in the sensitivities of the species and highlighted the need for data on multiple species, when estimating the effect of sediment pollution on the benthic community.…”
Section: Discussionmentioning
confidence: 89%
“…from different trophic and organizational levels [23,[35][36][37]. Tuikka et al [23], who investigated seven natural sediments using a test battery similar to that of the present study (SCTs with invertebrates, fish, and bacteria), demonstrated differences in the sensitivities of the species and highlighted the need for data on multiple species, when estimating the effect of sediment pollution on the benthic community.…”
Section: Discussionmentioning
confidence: 89%
“…A bioluminescence (BL) inhibition assay using Vibrio fischeri is often chosen as the first screening method in a test battery, based on speed and cost considerations [1][2][3]. V. fischeri has been used for more than 30 years in whole effluent toxicity testing (WET) [4], waste water treatment efficiency evaluation [5,6], surface water and sediment quality monitoring [7][8][9], ground water studies [10], risk assessment [11], and also as a model organism for fundamental studies on mode of action and toxicological pathways of various substances and mixtures [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the quality status of aquatic habitats, it has long been shown that particular attention must be paid to the chemical and ecotoxicological characterization of sediments (Cleveland et al 1997;Pederson et al 1998;Ghirardini et al 1999;Davoren et al 2005) because the sediment compartment acts as a sink and source of internal contaminant load posing a permanent threat to resident biota. Contaminants accumulated in the sediment have the potential to remobilize, and thus become bioavailable, after chemical (e.g., pH, salinity fluctuations), physical (e.g., dredging), or biological (e.g., bioturbation) processes (Davoren et al 2005).…”
mentioning
confidence: 99%
“…Contaminants accumulated in the sediment have the potential to remobilize, and thus become bioavailable, after chemical (e.g., pH, salinity fluctuations), physical (e.g., dredging), or biological (e.g., bioturbation) processes (Davoren et al 2005). For the ecotoxicological evaluation of sediments, various acute and chronic bioassays have been developed, standardized, and successfully applied: Toxicity tests with bacteria and unicellular algae, crustacean bioassays, tests based on sediment-dwelling organisms, fish toxicity tests, etc.…”
mentioning
confidence: 99%